Monetary Stability (Concepts and Implications) - Ayal Fattan, Muzna; Jaber, Ali (International Journal of Psychosocial Rehabilitation, 2020)
In order for criticism to perform its functions, it must enjoy stability over time, whether in terms of its value or where it exists. The stability of criticism translates to confidence in the minds of people and its adoption in their decisions that relate to the future. Also, monetary stability is one of the important indicators that the International Monetary Fund has adopted to demonstrate the stability of the state's economic situation and believes that the stability of cash is an inevitable means for the conduct of economic activity through the main ways and methods that would set the economic entity a program to address problems that threaten stability, which is summed up in several imbalances such as excessive inflation, volatility and instability in interest rates, exchange rates, and the balance of payments. And monetary stability is the stability of prices (interest rates, product prices and exchange rates) over time, within the framework of market freedom in the sense that there is a consistent proportion between the output The national and the monetary mass, so every increase or decrease in the monetary mass that is not matched by a similar increase or decrease in the national product leads to a disturbance of this stability.